Reflecting Religious Beliefs on Mummification in Ancient Egypt 1567-1085 BC (Raparin Journal of Humanities (RJH), 2021)
This study titled (reflecting religious beliefs on mummification in ancient Egypt 1567-1085 BC), is a scientific activity that focuses on the influence of religious beliefs on the practice of mummification. The Egyptians believed that they would await a better life after death, especially the kings, who would go before the gods and appoint rewards and punishment for them, so they considered it necessary. A protect and mummification body to reach his stage in the second world, all steps of mummification and burial have been done by religious men and with the consent of the gods.